Shoulder Angle During Ball Release Are Predictors of Ball Velocity Among Medium Pace Bowlers - Narvariya, Pushpendra; Singh, Joseph (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2022)
The purpose of the study. The aim was to find the effect of kinematic variables on ball velocity of medium pace bowlers. Materials and methods. A total of 10 male cricket players who were right arm medium pace bowlers were selected for this study. The kinematic variables selected in this study were wrist angle, elbow angle, shoulder angle, hip angle, knee angle, ankle angle, and centre of gravity. Results. A regression equation with R2 value of 0.616 was obtained from the study, i.e., 52.266+0.371 × (right shoulder angle). Conclusions. The study suggests shoulder angle to be important factor in determining ball velocity among medium pace bowlers